QUERCETIN IN PROPHYLAXIS OF QT INTERVAL DISPERSION INCREASING IN ACUTE ANTHRACYCLINE CARDIOTOXICITY - Keting, E.V.; Goncharenko, T.S.; Vatutin, N.T. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The anthracyclines are known to be the effective antineoplastic antibiotics which administration is limited because of severe cardiac damage. The aim of this study was to assess the effectiveness of antioxidant quercetin in preventing  the anthracycline acute cardiotoxicity by evaluating of ventricular repolarization dispersion. 43 рatients were examined (including ECG) before and 30 minutes after anthracycline injection. 21 patients among them were administered quercetin infusion before anthracycline. All the patients who got anthracyclines had the significant increasing of ΔQT, ΔQTc and ΔJT in comparing with the control group. However quercetin prevented further increasing of the ventricular repolarization inhomogeneity.